2006
DOI: 10.1038/sj.jid.5700117
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts Show More Potential as Target Cells than Keratinocytes in COL7A1 Gene Therapy of Dystrophic Epidermolysis Bullosa

Abstract: Dystrophic epidermolysis bullosa (DEB) is an inherited blistering skin disorder caused by mutations in the type VII collagen gene (COL7A1). Therapeutic introduction of COL7A1 into skin cells holds significant promise for the treatment of DEB. The purpose of this study was to establish an efficient retroviral transfer method for COL7A1 into DEB epidermal keratinocytes and dermal fibroblasts, and to determine which gene-transferred cells can most efficiently express collagen VII in the skin. We demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 24 publications
(33 reference statements)
0
73
0
1
Order By: Relevance
“…The long size of the COL7A1 cDNA hinders the generation of high-titer vectors (Goto et al, 2006;Siprashvili et al, 2010;Titeux et al, 2010). In our study, the titer obtained with the HA-COL7A1 vector from the 293Vec-Ampho population was 2 × 10 5 ivp/mL.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The long size of the COL7A1 cDNA hinders the generation of high-titer vectors (Goto et al, 2006;Siprashvili et al, 2010;Titeux et al, 2010). In our study, the titer obtained with the HA-COL7A1 vector from the 293Vec-Ampho population was 2 × 10 5 ivp/mL.…”
Section: Discussionmentioning
confidence: 79%
“…As described in our study for RDEB cells (Fig. 4), and by others (Georgiadis et al, 2016;Goto et al, 2006;Jackow et al, 2016;Titeux et al, 2010), transduced fibroblasts produced COLVII that relocated at the DEJ. However, the long-term persistence of these cells in our TESs remains to be proven.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Several studies have targeted keratinocytes, because the cells that secrete COL7 are mainly keratinocytes and to a lesser extent fibroblasts. 5,6 However, we and others have recently reported that injection of gene-transferred fibroblasts into the skin can efficiently restore COL7 expression in the dermal-epidermal junction in vitro. 6 -8 Furthermore, intradermal injection of allogeneic fibroblasts into skin of patients with RDEB skin was shown to result in enhanced COL7 expression in selected patients.…”
mentioning
confidence: 99%